2018
DOI: 10.3390/molecules23123340
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ERK1/2 and Akt Pathways Involved in the Neurotrophic Action of Caffeic Acid Alkyl Esters

Abstract: Neurodegenerative diseases affect millions of human lives all over the world. The number of afflicted patients is rapidly growing, and disease-modifying agents are urgently needed. Caffeic acid, an important member of the hydroxycinnamic acid family of polyphenols, has considerable neurotrophic effects. We have previously shown how caffeate alkyl ester derivatives significantly promote survival and differentiation in neuronal cells. In this study, the mechanisms by which these ester derivatives exert their neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
(67 reference statements)
2
4
0
Order By: Relevance
“…Since previous reports demonstrated an involvement of inhibition of calpains and activation of PI3-K/Akt intracellular pathway in neuroprotection mediated by caffeic acid- and its derivatives [ 6 , 22 , 23 ], we verified these mechanisms in our study by using calpain (MDL28170) and PI3-K (LY294002) inhibitors. We showed that cytoprotection mediated by MC was more robust than that mediated by MDL28170 (20 μM) and has not been changed after combined treatment with both compounds ( Table 1 ).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Since previous reports demonstrated an involvement of inhibition of calpains and activation of PI3-K/Akt intracellular pathway in neuroprotection mediated by caffeic acid- and its derivatives [ 6 , 22 , 23 ], we verified these mechanisms in our study by using calpain (MDL28170) and PI3-K (LY294002) inhibitors. We showed that cytoprotection mediated by MC was more robust than that mediated by MDL28170 (20 μM) and has not been changed after combined treatment with both compounds ( Table 1 ).…”
Section: Resultssupporting
confidence: 68%
“…Moreover, in the present study we found that the calpain inhibitor, MDL28170 protected cells against oxidative stress-induced cell damage to a smaller extent than MC and the protection range was not changed after administration of both compounds which suggests possible involvement of calpain inhibition in the MC-mediated neuroprotection. There are conclusive data showing the participation of activation of the pro-survival PI3-K/Akt pathway in the neuroprotective effects of CA and/or its derivatives [ 5 , 6 , 7 , 22 ]. However, in our study the inhibitor of PI3-K, LY294002 failed to block the neuroprotective effects of MC in the H 2 O 2 model of cell damage which excludes the participation of this signaling pathway in the MC-mediated neuroprotection at least in this model of neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the cells were further cultured for 4 h in 96-well plates in mediums with or without samples (100 μM resveratrol, 2 or 20 μM quercetin, and 2.5 or 25 μM caffeic acid) under 5% CO 2 at 37 °C. The concentrations of these three compounds were determined with reference to the papers [10,[25][26][27]. Similarly, according to the experimental results of Oike and Kobori, the sample processing time was set to 4 h [10].…”
Section: Cell Culturementioning
confidence: 99%